Large skin defect in Type V aplasia cutis congenita treated with conservative treatment: a case report - Yan song; Ru yang; Zeyao shi; Jing yan; Shulin hou; Xiaowen li; Xiufang zhao (BMC, 2024)
Abstract Aplasia cutis congenita (ACC) is a congenital disorder that can be classified into nine types, with Type I ACC being the most common. Type V ACC associated with fetus papyraceus is a rare subtype of ACC. We report the case of a Type V ACC in a male newborn with extensive abdominal skin defects. The patient received conservative treatment using hydrogel foam and silicone foam dressings. Approximately five weeks later, the patient was discharged when more than 60% of the skin had completed epithelialization. After discharge from West China Second University Hospital, Chengdu , the patient continued to be followed up regularly at the Burns and Plastic Surgery Clinic at local hospital in Gansu. We followed up the child by telephone. After 4 months of follow-up, scar tissue formation was observed in the trunk area. The infant is 2 years and 5 months old now, physical examination did not reveal any organ problems.